Evaluation of Th9 lymphocytes in peripheral blood of rheumatoid arthritis patients and correlation with anti-tumor necrosis factor therapy: results from an in vitro pivotal study - R. Talotta (Reumatismo, 2016)
The aim of this study was to determine the prevalence of T helper 9 (Th9) lymphocytes in rheumatoid arthritis (RA) patients and to identify a possible association between the percentage of Th9 and the discontinuation of a biological treatment with an anti-tumor necrosis factor (TNF) (infliximab). We collected peripheral blood mononuclear cells (PBMCs) from 55 consecutive RA outpatients and 10 healthy controls. Among RA patients, 15 were not receiving any immunosuppressive drug, 20 were successfully treated with infliximab and 20 discontinued infliximab because of adverse events or inefficacy and were treated with other biological agents. PBMCs were cultured with/without infliximab 50 mg/L for 18 h, and the percentage of Th9 cells was assessed by means of flow cytometry. Th9 lymphocytes were identified as interferon gamma, interleukin (IL)4-, IL17-, IL9-secreting cluster of differentiation 4 (CD4)+ T cells. Cytometric analysis revealed no significant decrease in the percentage of Th9 cells after infliximab exposure in any of the groups, although it was lower in healthy controls than RA patients either before and after the infliximab stimulation assay. Th9 cells are IL-9-secreting T helper lymphocytes whose role in RA is still poorly known. IL-9 levels are increased in RA patients, in whom this cytokine plays a crucial role. Th9 cells are the major producers of IL-9, and their prevalence is higher in RA patients than in healthy subjects; however our experiment in vitro does not demonstrate an association between Th9 lymphocytes and the response to infliximab. Further studies are required to evaluate the real involvement of Th9 population in the immunogenicity of anti-TNF agents.